Science to the Rescue? - Smallman, Melanie (Social Research)
During difficult times, many argue that science will come to our rescue. Investment in science, technology, data, and innovation is seen to be vital if we are to tackle the most pressing concerns facing society. But not everyone shares this enthusiasm: Whether it be anti-vaxxers or climate change deniers, there has been an increased adoption of populist views that seemingly reject the rationalism of science. This rise is not evidence of a public rejection of rational thinking, however, but rather a growing difference in the way people experience the effects of science and technology. Rather than a perceived crisis of trust, our biggest source of concern should be the different ways that technology shapes our worlds.